PERAN EDUPRENEURSHIP DALAM MENGEMBANGKAN LAYANAN BIMBINGAN BELAJAR UNTUK PENINGKATAN MUTU PENDIDIKAN - Ramadhina Qurrota Ayun; Shiva Amiliya Aidah; Nurul Ilma Aulia; Rizki Latifatun Nisa; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study explores the role of edupreneurship in developing tutoring services as an effort to enhance the quality of education. Employing a qualitative approach through literature review and direct observation, this research investigates how edupreneurship integrates entrepreneurial values into educational practices, particularly through the Fun Smart Kids tutoring program. The findings indicate that edupreneurship significantly contributes to improving learning quality by implementing creative and innovative strategies, such as the use of flipbooks, interactive quizzes, educational videos, and storybooks. These approaches effectively increase students’ enthusiasm, self-confidence, and understanding of school materials. Furthermore, the tutoring program not only benefits students in enhancing their academic performance but also provides valuable experience for tutors in managing educational services based on entrepreneurial principles. Therefore, edupreneurship serves as a sustainable approach to support the improvement of education quality while fostering creativity, innovation, and leadership skills among future educators. Practically, the results of this study can be used as a reference for schools and educational institutions in designing entrepreneurship-based learning programs that are more creative and impactful